Variation of bleeding time and clotting time in the ABO blood groups - Adhikari Manandhar, Seerina; Amatya, Mrigendra (Journal of Physiological Society of Nepal, 2020)
Introduction: Blood grouping, bleeding time (BT) and clotting time (CT) are important hematological parameters investigated before any surgical procedure. The association of blood groups with many diseases are established, such as epistaxis with blood group “O”. This study aimed to assess the relationship of BT and CT among different blood groups and to find any gender difference in these parameters. Materials and methods: A cross-sectional observational study was conducted among healthy medical students. Blood grouping was done by agglutination method, BT by Duke’s method, and CT by capillary tube method. Mean bleeding and clotting times (seconds) were compared among groups. Results: The study was completed in 351 students (160 males, 191 females), with age ranging from 19-23 years. Both BT and CT values were highest in the blood type O, BT was lowest in type B, and CT was lowest in type AB, although the differences were statistically not significant (p>0.15). Females had higher values of BT as well as CT than males (p values <0.001). A very highly significant correlation between the bleeding and clotting times was also noticed (Pearson’s correlation coefficient, P = 0.495, p<0.001). Conclusions: The study hinted a tendency for higher risk for hemorrhagic condition and lower risk for thrombotic event in blood group O compared to groups A, B or AB. Multicentric study including larger population with the emphasis on finding plasma vWF level may be helpful to verify findings, identify the risk groups, and take prior preventive measures.